EKSISTENSI DAN KONSTITUSIONALITAS PIDANA MATI MENURUT UUD 1945 BERKAITAN DENGAN TUJUAN HUKUM ISLAM - Muhammad, Abdul Azis; Sodikin, Sodikin (Faculty of Law, Universitas Diponegoro, 2024)
The death penalty has unique characteristics that are different from other forms of punishment. The aim of being studied is to know the existence and constitutionality of the death penalty concerning the objectives of Islamic law This research uses doctrinal research with a legislative approach and decisions regarding the death penalty. The results of this research explain that the application of the death penalty as a form of punishment known in Indonesian criminal law is in harmony with the 1945 Constitution of the Republic of Indonesia and its existence is by Islamic Law. The death penalty in Islamic law states that the concept of the objectives of Islamic law contained in the 1945 Constitution of the Republic of Indonesia is the concept of maqashid sharia which can be used as an alternative in resolving legal problems in society